Penerapan Nilai-nilai Berkelanjutan dalam Pendidikan Perubahan Iklim: Sebuah Kajian Epistemologi dan Aksiologi - Puspa Nuwangi, Pohaci; Nahadi; Anwar, Sjaeful; Riandi (Paradigma: Jurnal Filsafat, Sains, Teknologi, dan Sosial Budaya, 2023)
This research aims to examine the integration of education for sustainable development (ESD) values in climate change education (CCE) (CCESD) from an epistemological perspective, namely focusing on history and the development of those knowledges; and an axiological perspective, namely the values that build it. The research was carried out qualitatively using a literature study method, where all documents used as data sources were reading material that discussed "education for sustainable development", "climate change education", "epistemology", and "axiology". The results of the study show that ESD and CCE grow together from human anxiety about an uncertain future due to various problems with long-term impacts, such as climate change. Therefore, both aim to form a prosperous society and intergenerational justice. The two main characteristics of ESD values integrated in CCE are interdisciplinary integration and temporal connection between the past, present and future. In teaching ESD in CCE or CCESD, it is recommended to emphasize some key competencies of ESD: systems thinking competency, critical thinking competency, collaborative competency, integrative problem-solving competency, and anticipatory competency.